Possum come a-knockin - Van Laan, Nancy.; Booth, George (Knopf, 1990)
A cumulative tale in verse about a mysterious stranger that interrupts a family's daily routine.
A cumulative tale in verse about a mysterious stranger that interrupts a family's daily routine.
Keywords: Stories in rhyme. / http://id.loc.gov/authorities/subjects/sh2005008473; Opossums / Juvenile fiction.; Families / Juvenile fiction. / http://id.loc.gov/authorities/subjects/sh2008103507